Cover Image, Volume 172C, Number 4, December 2016. Issue 4 (December 2016) - Unknown
Abstract : The cover, by Vijay G. Sankaran et al., is based on Research Review the Emerging cellular and gene therapies for congenital anemias, DOI:10.1002/ajmg.c.31529 .